My American Uncle, America Cries Uncle, and Other Fantastic Tales from France: Iegor Gran's Jeanne d'Arc fait tic-tac - Carolyn A. Durham (Studies in 20th & 21st Century Literature, 2008)
Ella Shohat and Robert Stam's proposal that beliefs about nations often crystallize in the form of stories could serve as both summary and generative matrix for Jeanne d'Arc fait tic-tac. In keeping with a number of recent fictional works united by the attempt to understand French and American cultures in a comparative context, the first part of Iegor Gran's clever 2005 novel consists of eleven stories whose common focus on the danger represented by American culture for French national identity makes the second part of the novel, in which France declares war and invades the United States, almost inevitable. In the opening section of Jeanne d'Arc, Gran both rewrites the traditional folktale for a self-reflective postmodern age and revises and satirizes the conventions of fantastic literature. The primary comic strategy of the second half of the novel, constructed as a parody of the current American conflict in Iraq, pays homage to the most recent source of tension between the United States and France. Throughout the novel Gran caricatures French chauvinism and insularity as much as he mocks American arrogance and consumerism, and the metaphorical demise of the "oncle d’Amérique,” the specifically French version of the American dream, continually reminds us of the sheer power and pleasure of narrative.
Keywords: Ella Shohat; Robert Stam; Jeanne d' Arc fait tic-tac; French culture; American culture; French national identity; postmodern; satire; parody; comic; French chauvinism; American arrogance; American consumerism; oncle d’Amérique; American Dream